Endoscopic repair of the anterior skull base -is there a learning curve?. (4th July 2018) - Nix, Paul; Alavi, Seyed A.; Tyagi, Atul; Phillips, Nick
Abstract: Introduction: Endoscopic anterior skull base surgery is now established practice. For skull base teams to manage complex pathology a variety of good dural repair techniques are required. However repairing certain skull base defects can be challenging. We look to see if a learning curve is associated with different types of CSF leaks in the anterior skull base Methods: Analysis of a prospectively collected database, contain 383 cases, on all endoscopic anterior skull base operations at one UK institution looking at CSF repair. Chi squared statistical analysis was undertaken comparing results from 2009 to 2013 with the 2014 to 2017 results. CSF leaks were categorised as either low flow with defects less than 2cm in diameter or high flow with defects greater than 2cm in diameter associated with a CSF void. Results: 137 cases requiring repair were identified. Overall 96% of cases underwent successful primary repair with low flow CSF defects. The primary repair rate was similar in the early and later years. Successful repair of large anterior skull base defects was statistically more likely in the 2014-2017 group 96% compare to the 2009–2013 group 65%. Conclusions: A learning curve for small defects was not seen. However a learning curve does exist in relation to large defects with high flow over the first 20 cases.